Skin Grafting Impairs Postsynaptic Cutaneous Vasodilator and Sweating Responses - Davis, Scott L. (2007)
This study tested the hypothesis that postsynaptic cutaneous vascular responses to endothelial-dependent and -independent vasodilators, as well as sweat gland function, are impaired in split-thickness grafted skin 5 to 9 months after surgery. Intradermal microdialysis membranes were placed in grafted and adjacent control skin, thereby allowing local delivery of the endothelial-dependent vasodilator, acetylcholine (ACh; 1 × 10(−7) to 1 × 10(−1) M at 10-fold increments) and the endothelial-independent nitric oxide donor, sodium nitroprusside (SNP; 5 × 10(−8) to 5 × 10(−2) M at 10-fold increments). Skin blood flow and sweat rate were simultaneously assessed over the semipermeable portion of the membrane. Cutaneous vascular conductance (CVC) was calculated from the ratio of laser Doppler-derived skin blood flow to mean arterial blood pressure. ΔCVC responses from baseline to these drugs were modeled via nonlinear regression curve fitting to identify the dose of ACh and SNP causing 50% of the maximal vasodilator response (EC(50)). A rightward shift in the CVC dose response curve for ACh was observed in grafted (EC(50) = −2.61 ± 0.44 log M) compared to adjacent control skin (EC(50) = −3.34 ± 0.46 log M; P = .003), whereas the mean EC(50) for SNP was similar between grafted (EC(50) = −4.21 ± 0.94 log M) and adjacent control skin (EC(50) = −3.87 ± 0.65 log M; P = 0.332). Only minimal sweating to exogenous ACh was observed in grafted skin whereas normal sweating was observed in control skin. Increased EC(50) and decreased maximal CVC responses to the exogenous administration of ACh suggest impairment of endothelial-dependent cutaneous vasodilator responses in grafted skin 5 to 9 months after surgery. Greatly attenuated sweating responses to ACh suggests either abnormal or an absence of functional sweat glands in the grafted skin.